Performance of National Agricultural Advisory Services projects in Uganda: Does stakeholder commitment matter? - Bashir, Hassan; Namagembe, Sheila; Nangoli, Sudi; Ntayi, Joseph M.; Ngoma, Mohammed (World Journal of Entrepreneurship, Management and Sustainable Development, 2013)
The increased poor performance of National Agricultural Advisory Services (NAADS) projects in Uganda has become a concern of many stakeholders. Many NAADS projects have been undertaken with an aim of developing the poor in the country but none of them were successful. This paper therefore aimed at examining the performance of NAADS projects which were set up by the government in 2001 to eradicate poverty in Uganda. Design/methodology/approach – The study adopted a cross-sectional and quantitative survey research design. Data was sought from farmers and coordinators of the projects. Mukono district was used as a case study and a sample of 323 NAADS projects were used, covering a wide range of agricultural activities. Findings – The research findings showed low performance levels of the NAADS projects and raised pertinent questions on the influence of NAADS stakeholders’ commitment to the performance of the projects. It was there recommended that an urgent review of NAADS policy and practices be done to ensure that project managers and coordinators discuss with farmers the personal benefits of carrying out activities of NAADS such that farmers fill a great deal of personal meaning of the project to their lives. Originality/value – This is the first study to document the effect of stakeholder commitment on the performance of National Agricultural Advisory Services projects in Uganda. The poor people in Uganda have really not been committed to the NAADS projects despite the willingness of the government to take them out of poverty. One of the reasons is that they don’t see themselves achieving any benefits from these projects, the projects require high costs of agricultural extension services which cannot be afforded by the farmers and also because the poor people lack farmer groups to participate in the NAADS projects. Rural farmers look as if they do not have technical or professional connections to participate and take advantage of the projects.
Keywords: NAADS; Project performance; Stakeholder commitment; Project management